Pseudomalignancies of the head and neck. Issue 5 (May 2021) - Crane, Hannah; Walsh, Hannah; Tailor, Artysha; Hunter, Keith
Abstract: Pseudomalignancies are benign or reactive lesions that mimic malignant neoplasms either clinically or histologically. In the head and neck region there are a number of pseudomalignancies that may present to a histopathologist, including soft tissue lesions, benign odontogenic tumours and salivary gland pathology. In this review we discuss common pseudomalignant lesions that may present in the head and neck, including their clinical presentation, histopathological features and differential diagnosis.